A pooled analysis of breast-feeding and breast cancer risk by hormone receptor status in parous Hispanic women - Sangaramoorthy, Meera (Epidemiology, 2019)
BACKGROUND: Data on breast-feeding and breast cancer risk are sparse and inconsistent for Hispanic women. METHODS: Pooling data for nearly 6,000 parous Hispanic women from four population-based studies conducted between 1995 and 2007 in the U.S. and Mexico, we examined the association of breast-feeding with risk of breast cancer overall and subtypes defined by estrogen receptor (ER) and progesterone receptor (PR) status, as well as the joint effects of breast-feeding, parity, and age at first birth. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) using logistic regression. RESULTS: Among parous Hispanic women, older age at first birth was associated with increased breast cancer risk, whereas parity was associated with reduced risk. These associations were found for hormone receptor positive (HR+) breast cancer only and limited to premenopausal women. Age at first birth and parity were not associated with risk of ER-PR-breast cancer. Increasing duration of breast-feeding was associated with decreasing breast cancer risk (≥25 vs. 0 months: OR=0.73, 95% CI=0.60–0.89, P(trend) =0.03), with no heterogeneity by menopausal status or subtype. At each parity level, breast-feeding further reduced HR+ breast cancer risk. Additionally, breast-feeding attenuated the increase in risk of HR+ breast cancer associated with older age at first birth. CONCLUSIONS: Our findings suggest that breast-feeding is associated with reduced risk of both HR+ and ER-PR-breast cancer among Hispanic women, as reported for other populations, and may attenuate the increased risk in women with a first pregnancy at older ages.